Ruthenium(II)/Chiral Carboxylic Acid Catalyzed Enantioselective C–H Functionalization of Sulfoximines - Huang, Long-Tao; Hirata, Yuki; Kato, Yoshimi; Lin, Luqing; Kojima, Masahiro; Yoshino, Tatsuhiko; Matsunaga, Shigeki (Synthesis, 2021)
Ruthenium(II)-catalyzed enantioselective C–H functionalization reactions of sulfoximines with sulfoxonium ylides are described. The combination of [RuCl2(p-cymene)]2 and a pseudo-C2-symmetric binaphthyl monocarboxylic acid furnished the S-chiral products in 76:24 to 92:8 er.
Keywords: ruthenium catalysis; C–H activation; asymmetric catalysis; chiral carboxylic acid; sulfoximine